Multi-stage and multi-compartment model for dynamic simulation of horizontal fluidized bed granulator - Mielke, Lisa; Bück, Andreas; Tsotsas, Evangelos (Drying Technology, 2019)
This work presents a multi-chamber and multi-compartment model of a horizontal fluidized bed apparatus for layering granulation, coating, and drying. Each chamber is designed individually and process conditions, such as spray rate, particle feed or gas temperature, can be adjusted for each chamber separately. Particle growth is described by population balance modeling. The characteristics of the particle exchange rates between the individual process chambers are determined by separation functions to account for different weir configurations. Additionally a drying model is presented that takes initial droplet size and contact angle as well as partial wetting of the particle surface into account. Because of the great variety of parameters that influence this model, a parametric study is carried out to identify how construction or process parameters affect the product quality. The influence of different separation functions, thermal process conditions, and initial droplet properties on key product quality features such as particle size distribution, product moisture content, and degree of surface wetting are presented and discussed. The developed model can be used to describe product quality and particle transport in complex horizontal fluidized bed apparatuses.
CRIS-Team WoS Importer:2019-12-17